Operation of Transformer Less On-Line UPS using Sinusodial Pluse with Modulation (SPWM) Technique and Its Simulation: A study on the operation and simulation of Transformer Less On-Line UPS using Sinusodial Pulse with Modulation technique (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In 21st century static uninterruptable power supply systems are very commonly used. They have a very wide variety of applications in low, medium and high power like as modern computer, CNC and VMC machinery and textile machinery. UPS is becoming more popular because its efficiency is higher comparatively lower total harmonic distortion and reliable operation. This paper presents the operation and its results of simulation using software tool of Transformer less On-line UPS.